Penentuan Keunggulan Kompetitif Pemasaran Teh Melalui Audit Strategi Marketing Plus (Kasus Pada PT. Perkebunan Nusantara VIII Jawa Barat) - Utan Sahiro Ritonga (Paspalum: Jurnal Ilmiah Pertanian, 2018)
The goal of this research is to measure the competitive advantage in tea marketing with a case study on PT. Perkebunan Nusantara VIII West Java, and describing the deciding factors in the improvement of competitive advantage in tea marketing competition. The method used in this research is case study with quantitative approach using marketing plus strategy audit by comparing the values of Company Alignment Index (CAI) and Competitive Setting Index (CSI). The calculation of both indexes is obtained from questionnaires about the confidence level of the respondents who manage the marketing policies of PT. Perkebunan Nusantara VIII. By comparing CSI value which is consisted of Customer (C1), Competitor (C3), Change-Driven (C4) against CAI which is consisted of Company (C2) which would be the measure of the competitive advantage of the company’s marketing strategy. From the analysis results, it can be seen that a negative gap of -1.09 where the value of CAI < CSI would mean that the company does not possess the competitive advantage in tea marketing strategy, and is relatively left behind in terms of tea industry competition. It can be learned that the cause of such low score in tea marketing strategy is caused by the low score of segmentation = 1 in the strategy, value with a score of 1.72 in the process, tactics which is consisted of differentiation = 2.63 and marketing mix = 2.63. To achieve competitive advantage in an ideal markting strategy, the factors that contribute to the marketing strategy competitive advantage value should be considered in the implementation of tea marketing strategy.